1999
DOI: 10.1111/1467-985x.00130
|View full text |Cite
|
Sign up to set email alerts
|

The Zero-Inflated Poisson Model and the Decayed, Missing and Filled Teeth Index in Dental Epidemiology

Abstract: For frequency counts, the situation of extra zeros often arises in biomedical applications. This is demonstrated with count data from a dental epidemiological study in Belo Horizonte (the Belo Horizonte caries prevention study) which evaluated various programmes for reducing caries. Extra zeros, however, violate the variance±mean relationship of the Poisson error structure. This extra-Poisson variation can easily be explained by a special mixture model, the zero-in¯ated Poisson (ZIP) model. On the basis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
243
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(249 citation statements)
references
References 16 publications
3
243
0
Order By: Relevance
“…This approach is similar to the specification of zero-inflated models (Böhning et al, 1999). Even though the component specific densities are in general assumed to be from the same parametric family (e.g.…”
Section: Model Specificationmentioning
confidence: 99%
“…This approach is similar to the specification of zero-inflated models (Böhning et al, 1999). Even though the component specific densities are in general assumed to be from the same parametric family (e.g.…”
Section: Model Specificationmentioning
confidence: 99%
“…Zero-inflated count models (Mullahy, 1986;Lambert, 1992) account for this data characteristic and are frequently used in the literature. Among others, Grootendorst (1995) analyses prescription drug utilisation, Street et al (1999) examine data on pharmaceutical utilisation and expenditure in Russia and Böhning et al (1999) consider caries prevention in dental epidemiology.…”
Section: Introductionmentioning
confidence: 99%
“…However this method assumes the equidispersion of the data (Bohning et al, 1999). Unfortunately this assumption is often violated in the observed data because data are often overdispersed.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them are Lestari (2008) modeled counts data of commercial sex worker at Clinic for human reproduction, Putat Jaya, Surabaya; Bohning et al (1999) used ZIP to analyze counts data on prevention of dental caries in children; and Mouatassim and Ezzahid (2012) fitted models to the number of claims in a private health insurance scheme. Those research themes showed that ZIP Regression fitted counts data better than Poisson Regression.…”
Section: Introductionmentioning
confidence: 99%